Foot massage and warm foot soak for lowering blood pressure in pregnant women with hypertension - Tompunuh, Magdalena Martha; Yulianingsih, Endah; Porouw, Hasnawatty Surya; Sujawaty, Sri; Wahyudi, Nanda (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2025)
Background: Hypertension during pregnancy remains one of the leading causes of maternal morbidity and mortality worldwide, particularly in low- and middle-income countries. This condition increases the risk of complications such as preeclampsia, preterm birth, and placental abruption. As pharmacological treatments may pose risks to both the mother and fetus, non-pharmacological interventions have gained interest as safer complementary approaches to managing hypertension in pregnancy. Objectives: The purpose of this study was to evaluate and compare the effectiveness of foot massage therapy and warm water foot soaks in reducing blood pressure among pregnant women diagnosed with hypertension.Methods: A quasi-experimental study with a non-equivalent control group design was conducted involving 72 pregnant women with hypertension. Participants were selected through purposive sampling and divided into two groups: one group (n=36) received foot massage therapy, while the other group (n=36) underwent warm water foot soaks. Both interventions were administered over a specific period, and blood pressure was measured before and after each session. The Wilcoxon Signed Ranks test was used to assess within-group changes, while the Mann–Whitney U test evaluated differences between the groups.Results: The results demonstrated a statistically significant reduction in both systolic (p = 0.00) and diastolic (p = 0.02) blood pressure in the foot massage group. Conversely, the warm water foot soak group did not show significant changes in systolic (p = 0.021) or diastolic (p = 0.026) pressure. Comparative analysis revealed that foot massage therapy was significantly more effective than warm water foot soaks in lowering blood pressure.Conclusions: Foot massage therapy is a more effective non-pharmacological intervention than warm water foot soaks for reducing blood pressure in hypertensive pregnant women. It offers a simple, safe, and cost-effective complementary strategy that can be integrated into prenatal care practices to improve maternal health outcomes.